Construction of pad foundation - Abdul Razak, Muhammad Zameer Rifaie (Universiti Teknologi MARA, Perak, 2019)
Foundation is a part of structure which connects superstructures to the adjacent zone of soil or rock below it. The functions of foundations is to transfer and spread the loads from a structure's columns and walls as well as any load in the structure into the ground without exceeding safe bearing capacity of the soil. This report was conducted for the construction project of bungalow PT 10211 at Teluk Penchalang, Pasir Panjang, Perak. The objectives of this report is to study the process involve on the construction of pad foundation in the construction project. It will focus on the foundations that are built as a structure that supports the load from the structure.